The value of pay-for-performance in England: An evaluation of NHS England's Quality Outcomes Framework - Movva, N; Jani, A (2018)
Pay-for-performance models have been introduced in many systems to incentivize improvements in efficiency and quality. England's Quality Outcomes Framework (QOF), introduced in 2004, incentivizes primary care general practices (GPs) for their achievements in patient care based on pre-established structure, process, and outcome measures. This paper examines QOF from a value (outcomes/cost) lens and determines the extent to which QOF indicators address patient outcomes and if QOF led to service improvement from 2013-2016 for an indicator of coronary heart disease (CHD002). Only 10 of the 75 QOF indicators addressed patient outcomes and analyses of data provided by NHS Digital demonstrated that most populations remained stagnant or worsened between 2013-2016. Based on the results of this study, it was clear that QOF, in its current format, does not facilitate the delivery of higher value care. Re-examining the structure and use of QOF may prove beneficial to delivering higher value care in England.